From Medicus Philosophus to Medicus Religiosus, Or Why Wasn’t Medical Education Installed at the Vilnius Jesuit Academy - Pociūtė, Dainora (Problemos, 2020)
The article deals with the absence of medical studies at the Vilnius Jesuit Academy. The question in the historiography is linked rather with the local peculiarities than the Jesuit attitude toward medicine in particular. Some attempts to establish medical studies in Vilnius during the 16th and 17th centuries are discussed in the context of Early-modern Jesuit universities that forbade Jesuits to involve themselves in academic medicine. The exclusion of medicine from Jesuit schools is analyzed as an intentional dissociation from the rise of the learned medicine and early modern philosophical tendencies of the medicalization of the soul. Jesuits also introduced the pattern of medicus religiosus instead of medicus philosophus, which represented their image of medical practitioner.